Differences between Mycobacterium-Host Cell Relationships in Latent Tuberculous Infection of Mice Ex Vivo and Mycobacterial Infection of Mouse Cells In Vitro - Elena Ufimtseva (Journal of Immunology Research)
The search for factors that account for the reproduction and survival of mycobacteria, including vaccine strains, in host cells is the priority for studies on tuberculosis. A comparison of BCG-mycobacterial loads in granuloma cells obtained from bone marrow and spleens of mice with latent tuberculous infection and cells from mouse bone marrow and peritoneal macrophage cultures infected with the BCG vaccine in vitro has demonstrated that granuloma macrophages each normally contained a single BCG-Mycobacterium, while those acutely infected in vitro had increased mycobacterial loads and death rates. Mouse granuloma cells were observed to produce the IFNγ, IL-1α, GM-CSF, CD1d, CD25, CD31, СD35, and S100 proteins. None of these activation markers were found in mouse cell cultures infected in vitro or in intact macrophages. Lack of colocalization of lipoarabinomannan-labeled BCG-mycobacteria with the lysosomotropic LysoTracker dye in activated granuloma macrophages suggests that these macrophages were unable to destroy BCG-mycobacteria. However, activated mouse granuloma macrophages could control mycobacterial reproduction in cells both in vivo and in ex vivo culture. By contrast, a considerable increase in the number of BCG-mycobacteria was observed in mouse bone marrow and peritoneal macrophages after BCG infection in vitro, when no expression of the activation-related molecules was detected in these cells.